"Your westernized habits": contextual nuances of qualitative research in Russia. Issue 1 (17th May 2021) - Earl, Anna
Abstract : Purpose: Fieldwork in emerging economies can be unpredictable and somewhat dangerous. The purpose of this article is to ascertain problematic issues that may arise when conducting qualitative research in emerging economies. Design/methodology/approach: The author reflects on her fieldwork in Russia in 2014 and 2015. Specifically, the author provides a reflection on her investigation on how the Russian government influences Russian MNEs' ability to deal with domestic institutional complexity and gain external legitimacy. Findings: The author has encountered a number of unforeseen difficulties: the ethical dilemma, sensitivity of the topic, translation challenges and unexpected group interviews. Through this reflection, he develops specific tactics on how to deal with these circumstances when conducting research outside a Western context. He also provides recommendations on how researchers in emerging economies can deal with ethical dichotomy created by the pressure to follow ethical guidelines. Finally, he identifies a list of opportunities that Russia presents as a research site. Research limitations/implications: The reflections on fieldwork discussed in this paper can prove to be useful for qualitative researchers interested in conducting qualitative research in Russia. In particular, it provides specific recommendations on how to navigate Russia as a research site. Originality/value: This paper contributes to the literature on issues related to methodological issues related to conducting research in emerging economies, as well as under research contexts, such as Russia.